2021
DOI: 10.1002/ajh.26268
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anticoagulation on recurrent thrombosis and bleeding after hematopoietic cell transplantation

Abstract: History of venous thromboembolism (VTE) is prevalent among patients undergoing hematopoietic cell transplantation (HCT). Management of anticoagulation is particularly challenging as most patients will have chemotherapy-induced thrombocytopenia while awaiting engraftment post-HCT. We conducted a retrospective study of autologous and allogeneic HCT recipients with prior VTE from 2006-2015 to 1) compare anticoagulant strategies on short-term VTE recurrence and bleeding and 2) assess predictors for VTE recurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…17,63,64 For instance, in a well-designed retrospective study, neither proposed platelet transfusion threshold nor platelet count (stratified into platelet count categories using the area under the curve from all platelet counts during follow-up) were predictive of bleeding in patients with anticoagulation and TP postautologous HSCT. 64 Factors associated with bleeding in TP cancer patients are detailed in Table 4, including allogeneic or autologous HSCT, 52 and renal or liver dysfunction. 64 Accordingly, we recommend therapeutic-dose anticoagulation in most patients with grade 1-2 TP who have an indication for anticoagulation post-VTE (Figure 1).…”
Section: Adjustment Of Anticoagulationmentioning
confidence: 99%
See 1 more Smart Citation
“…17,63,64 For instance, in a well-designed retrospective study, neither proposed platelet transfusion threshold nor platelet count (stratified into platelet count categories using the area under the curve from all platelet counts during follow-up) were predictive of bleeding in patients with anticoagulation and TP postautologous HSCT. 64 Factors associated with bleeding in TP cancer patients are detailed in Table 4, including allogeneic or autologous HSCT, 52 and renal or liver dysfunction. 64 Accordingly, we recommend therapeutic-dose anticoagulation in most patients with grade 1-2 TP who have an indication for anticoagulation post-VTE (Figure 1).…”
Section: Adjustment Of Anticoagulationmentioning
confidence: 99%
“…Several cohort studies have shown that VTE frequently recurs soon after platelet count recovers in patients who do not restart anticoagulation. 52,71 A retrospective study of 250 patients postallogeneic HSCT demonstrated a relative 20% increase in VTE recurrence in patients with prior VTE (most subacute or remote) who did not restart anticoagulation after platelet engraftment, whereas the VTE rates were low during periods of grade 3-4 TP (median 14 d of grade 3-4 TP). 52 Therefore, among patients who have anticoagulation held or reduced during TP, we recommend resuming full-dose anticoagulation as soon as platelet count allows, if the indication persists.…”
Section: Adjustment Of Anticoagulationmentioning
confidence: 99%
“…Several cohort studies have shown that VTE frequently recurs soon after platelet count recovers in patients who do not restart anticoagulation. 52 , 71 A retrospective study of 250 patients postallogeneic HSCT demonstrated a relative 20% increase in VTE recurrence in patients with prior VTE (most subacute or remote) who did not restart anticoagulation after platelet engraftment, whereas the VTE rates were low during periods of grade 3–4 TP (median 14 d of grade 3–4 TP). 52 Therefore, among patients who have anticoagulation held or reduced during TP, we recommend resuming full-dose anticoagulation as soon as platelet count allows, if the indication persists.…”
Section: Anticoagulant Therapymentioning
confidence: 99%
“…6 Moreover, for those patients who develop VTE during HCT, the use of anticoagulation therapy is also associated with important rates of clinically significant and fatal bleeding. 1,7 Unfortunately, thrombocytopenia is not a protective factor for the development of VTE, with up to a third of events occurring when the platelet count is less than 50 Â 10 9 /L, and 13% with platelet counts less than 20 Â 10 9 /L. 1 There are no validated VTE risk stratification tools applicable to the HCT population that allow the appropriate selection and timing of pharmacological thromboprophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…Patients undergoing HCT, in particular allogeneic, often experience prolonged periods of thrombocytopenia, which predisposes them to a higher risk of clinically relevant hemorrhagic complications 6 . Moreover, for those patients who develop VTE during HCT, the use of anticoagulation therapy is also associated with important rates of clinically significant and fatal bleeding 1,7 . Unfortunately, thrombocytopenia is not a protective factor for the development of VTE, with up to a third of events occurring when the platelet count is less than 50 × 10 9 /L, and 13% with platelet counts less than 20 × 10 9 /L 1 …”
Section: Introductionmentioning
confidence: 99%